Life-cycle assessment of pyrolysis processes for sustainable production of biochar from agro-residues. (September 2022) - Zhu, Xiefei; Labianca, Claudia; He, Mingjing; Luo, Zejun; Wu, Chunfei; You, Siming; Tsang, Daniel C.W.
Graphical abstract: Highlights: Agro-residues are candidate feedstocks for sustainable production of biochar. Pyrolysis is a promising technology for net carbon management of agro-residues. LCA unification facilitates the sustainability assessment of biochar production. Biochar has carbon reduction potential in energy and soil applications. Biochar technologies with regional characteristics have great development prospects. Abstract: Net carbon management of agro-residues has been an important pathway for reducing the environmental burdens of agricultural production. Converting agro-residues into biochar through pyrolysis is a prominent management strategy for achieving carbon neutrality in a circular economy, meeting both environmental and social concerns. Based on the latest studies, this study critically analyzes the life cycle assessment (LCA) of biochar production from different agro-residues and compares typical technologies for biochar production. Although a direct comparison of results is not always feasible due to different functional units and system boundaries, the net carbon sequestration potential of biochar technology is remarkably promising. By pyrolyzing agro-residues, biochar can be effectively produced and customized as: (i) alternative energy source, (ii) soil amendment, and (iii) activated carbon substitution. The combination of life cycle assessment and circular economy modelling is encouraged to achieve greener and sustainable biochar production.